Retinal Screening of Prolactinoma Patients Using Flash Electroretinography - Keramti, Shahrzad; Javanshir, Salar; Tajik, Fatemeh; Shushtarian, Seyed Mohammad Masoud; Shojaei, Ahmad; Abolhasani, Abbas (Journal of Ophthalmology and Research, 2021)
Aim: Prolactinoma is the most pituitary adenomas that affect young women at fertile age. Visual impairment is a common presentation of this condition. Retina is a part of visual system may be affected in these patients. Flash electroretinography is one of the techniques to screen the retina. The aim of present work is to search for probable adverse effect of prolactinoma on retina using flash electro-retinography. Patients and Method: Fifteen female patients (30 eyes) with age range of 20-40 years were selected. The patients had healthy visual system as for as visual acuity, field of vision and magnetic resonance imaging of brain were concerned. The amplitude and latency of electroretinogram b-wave was recorded for these patients and 15 age and sex matched controls with healthy visual system. Results: The mean age was 29.4±6.68 and 29.13±6.82 in case and control groups respectively. The mean visual acuity was 0.00±0.00 (LogMar) in both groups. The difference in values were not statistically significant as far as age (P = 0.967) and visual acuity (P=1) were concerned. The values obtained for amplitude were 113.93 ± 9.14 and 114.4 ± 6.83 in case and control groups respectively. On other hand the values for latency were 34.13 ± 1.56 and 34.13 ± 1.65 in case and control groups respectively. The values for ERG were not statistically significant as for as amplitude and latency (P = 0.682 and P = 0.925 respectively) of ERG, b-wave were concerned. Conclusion: Prolactinoma does not affect retina of the patients as for as flash electroretinography is concerned.